Identification of functional groups and determination of carboxyl formation temperature in graphene oxide using the XPS O 1s spectrum - Kwan, Yue Chau Garen; Ng, Ging Meng; Huan, Cheng Hon Alfred (Thin solid films, 2015)
Experimental information on the O 1s spectra of GO by X-ray photoelectron spectrometry is limited and this will prove to be a liability when analyzing samples that have high carbon to oxygen ratios. Here, the binding energy (B.E.) information of electrons from the O 1s orbital of oxygen atoms in different functional groups were identified by characterizing GO in an in-situ heating and characterization experiment, performed in a vacuum between 473 and 573K, and chemically modified GO. The B.E.s of the O 1s electrons in hydroxyls, epoxides, carbonyls and carboxyls on GO were determined and carboxyl formation on GO was found to occur between 543 and 561K. Here, carboxyl formation is a decrease in the proportion of oxygen atoms bound to GO as hydroxyls and epoxides groups, accompanied by a greater than proportional increase in the proportion of oxygen atoms bound as carboxyls, and this results in the formation of vacancies on the graphene basal plane. •Identification of functional groups in graphene oxide from O 1s spectra•Identification of carboxylation temperature regime in graphene oxide•Verification of the functional groups by chemical modification of GO